The Influence of the Problem Based Learning Model on Learning Outcomes of the Properties of Light at SMP Negeri 1 Karanganyar - Aji , Indra Triwarna; Kusumadani, Annur Indra (Journal of Biology Learning, 2024)
Problem-based learning (PBL) is an instructional model that utilizes problems as a starting point for acquiring and integrating new knowledge. The purpose of this study was to determine the effect of the Problem-Based Learning (PBL) model on improving students' learning outcomes on the topic of light properties in eighth-grade students at SMP Negeri 1 Karanganyar during the 2022/2023 academic year. This research employed a quasi-experimental approach using a Randomized Control-Group Posttest-Only Design. Data collection methods included the administration of questionnaires, pretests and posttests, and oral interviews. Based on the results of the research, it can be concluded that the Problem-Based Learning model significantly influences students' learning outcomes on the topic of light properties. This is indicated by the t-test results, where tcount = 2.064 and ttable = 2.006 with df = 52. Since tcount > ttable (2.064 > 2.006), the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. These findings demonstrate that the Problem-Based Learning model has a significant positive effect on students' learning outcomes in the topic of light properties among eighth-grade students at SMP Negeri 1 Karanganyar during the 2022/2023 academic year.